Dog man no. 2 . dog man unleashed - Pilkey, Dav (New York GRAPHIX, 2016)
Publisher Annotation: Dog Man, the newest hero from the creator of Captain Underpants, is still learning a few tricks of the trade. Petey the cat is out of the bag, and his criminal curiosity is taking the city by storm. Something fishy is going on! Can Dog Man unleash justice on this ruffian in time to save the city, or will Petey get away with the purr-fect crime? Dog man series, 224pp., Color Ill
Comic Strips
1
Keywords: Cartoons and comics; Graphic novels